Subtle Mutagenesis by Ends-in Recombination in Malaria Parasites - Nunes, Alvaro (American Society for Microbiology, 1999)
The recent advent of gene-targeting techniques in malaria (Plasmodium) parasites provides the means for introducing subtle mutations into their genome. Here, we used the TRAP gene of Plasmodium berghei as a target to test whether an ends-in strategy, i.e., targeting plasmids of the insertion type, may be suitable for subtle mutagenesis. We analyzed the recombinant loci generated by insertion of linear plasmids containing either base-pair substitutions, insertions, or deletions in their targeting sequence. We show that plasmid integration occurs via a double-strand gap repair mechanism. Although sequence heterologies located close (less than 450 bp) to the initial double-strand break (DSB) were often lost during plasmid integration, mutations located 600 bp and farther from the DSB were frequently maintained in the recombinant loci. The short lengths of gene conversion tracts associated with plasmid integration into TRAP suggests that an ends-in strategy may be widely applicable to modify plasmodial genes and perform structure-function analyses of their important products.